Validation of new gas chromatography-flame ionization detection procedure for quantitation of residual solvents in [18F]FDG - Flávia Mesquita Costa; Cassiano Lino dos Santos Costa; Juliana Batista Silva; Soraya Maria Zandim Maciel Dias Ferreira (Brazilian Journal of Radiation Sciences)
Fludeoxyglucose F 18 ([18F]FDG) is the most used radiopharmaceutical for positron emission tomography, especially on oncology. Organic solvents such as ether, ethanol and acetonitrile might be used in the synthesis of [18F]FDG; however, they might not be completely removed during purification steps. The determination of residual solvents in [18F]FDG is required in the European Pharmacopoeia (EP) and the United States Pharmacopeia (USP) monographs. While the procedure described in the EP is quite general, the one described in the USP requires a long runtime (about 13 minutes). In this work a simple and fast (4-minute) analytical procedure was developed and validated for determination of residual solvents in [18F]FDG. Analyses were carried out by gas chromatography – flame ionization detector (GC-FID). The separation was obtained on a 0.53-mm x 30 m fused-silica column. Validation included the evaluation of various parameters, such as: specificity, linearity and range, limits of detection and quantitation, precision (repeatability and intermediate precision), accuracy, and robustness. Results were found to be within acceptable limits, indicating the developed procedure is suitable for its intended application. Considering the short half-life of fluorine-18 (109.7 minutes), this new method could be a valuable alternative for routine quality control of [18F]FDG.